A Fast and in-Situ Measuring Method Using Laser Triangulation Sensors for the Parameters of the Connecting Rod - Xing-Qiang Li; Zhong Wang; Lu-Hua Fu (Sensors, 2016)
The connecting rod is a critical part inside the marine engine. The inspection of its important parameters is directly related to the assembly and quality of the marine engine. A coordinate measuring machine (CMM) is a conventional choice to measure the parameters of a connecting rod. However, CMM requires significant resources in time and cost, which leads researchers into in-situ measurement. This article presents a fast and in-situ measuring method by using a laser-based measuring head. Two measuring strategies are adopted in the inspection process. For positional measurements (such as the hole–center distance), whose accuracy requirement is generally low, the coordinate system of the numerical control (NC) machine is combined with the measuring head to acquire the positional parameters. For dimensional measurements (such as inner diameters), whose accuracy requirement is rather high, the NC machine is used just as transportation. Note that the measuring head has the ability to perform the dimension inspection independently. The accuracy of the measuring head is high enough to meet the dimensional accuracy requirements. Experiments are performed to validate the proposed method. The measuring error of the inner diameters is from 5 μm to 7 μm. The measuring error of hole–center distance is within 15 μm. The measurement of all these parameters can be done within 1 min.